Man in Health and Disease. Prevention and Management of Civilizational Diseases: International Scientific Conference, May 24, 2024, Tarnów, Poland - Chwała, Wiesław; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2024)
Arthur Schopenhauer’s philosophical statement ‘while health is certainly not everything, without health everything is nothing’ prompts us to think deeply about its value. Probably we would all agree with Thomas Fuller that ‘illness is always an unexpected guest.’ That’s why it’s worth taking to heart the words of Pliny the Elder ‘take care of your health today, so that you don’t have to dream about it when you are in impotence.’ We give you another, the seventh study devoted to the dissemination of knowledge in the field of prevention of diseases of civilization, leveling their effects within a comprehensive management program. This time a significant place among the included studies is occupied by: the preventive aspect of pro-health education in civilization diseases, physical activity as an essential element of normal development and health, the risks and benefits to health arising from sports and recreation, a holistic approach in therapy and patient care, or the health of society in the face of threats of the 21st century. As a natural corollary to the experiences of past years, there were also emphases on assessing the impact of pandemics on the physical and mental health of individuals and entire communities, as well as reports on the use of AI in therapy. We hope that, like the previous conference papers, the present one will also provide an opportunity to learn about current scientific developments in the broad area of knowledge of the Health Sciences discipline and become a platform for the exchange of experiences at a high level of scientific discourse. We trust that the experience of previous years will be of great interest to health professionals, patients and the community. The knowledge and experience you will gain from reading the conference book of abstracts: Man in Health and Disease. Prevention and Management of Civilization Diseases, may it be a confirmation of the words of American writer Franklin Adams that ‘health is the factor that makes us feel that we are just at the best time of our lives.’ Let us appreciate its value and let this awareness be a strong motivation to strive for our own health, as much in this regard depends on ourselves. Head of Scientific Committee Wiesław Chwała